How servicesape affects diners' satisfaction and their behavioral intentions in family chain restaurants : a Malaysian case - Othman, Mohhidin; Goodarzirad, Bahar; Abdul Karim, Muhammad Shahrim (2010)
The concept of servicescape and its effect on customer satisfaction and behavioral intentions has been studied extensively in various areas of service retailing but not in the family branded restaurants in Malaysia. The aim of this paper is to fill in some of the research gap by testing the effects of servicescape (facility aesthetics, layout accessibility, seating comfort, ambient condition and cleanliness) on diners' satisfaction and behavior. Findings include the important role of functional and effective servicescape components in shaping diners' satisfaction and their behavioral intentions. Each dimension was identified as the determining attributes which strongly predicted the satisfaction and their important roles in the formation of future repatronage intentions. The finding also provides insights to the restaurants on the importance of servicescape in eliciting positive images of the restaurants. Hence, the restaurants will be able to better serve the customers and increase their satisfaction and revisit intentions.